2014
DOI: 10.2337/db13-0981
|View full text |Cite
|
Sign up to set email alerts
|

pH of Drinking Water Influences the Composition of Gut Microbiome and Type 1 Diabetes Incidence

Abstract: Nonobese diabetic (NOD) mice spontaneously develop type 1 diabetes (T1D), progression of which is similar to that in humans, and therefore are widely used as a model for understanding the immunological basis of this disease. The incidence of T1D in NOD mice is influenced by the degree of cleanliness of the mouse colony and the gut microflora. In this report, we show that the T1D incidence and rate of disease progression are profoundly influenced by the pH of drinking water, which also affects the composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
150
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(161 citation statements)
references
References 44 publications
8
150
2
1
Order By: Relevance
“…We did not perform monocolonization experiments in our system, and thus it is entirely possible that SFB acts here indirectly, as observed in models of colitis 13 or type 1 diabetes. 37 The most interesting result from this study, however, is the unique regulation of a T-cell intrinsic tolerance mechanism achieved by SFB-derived inflammatory signals. Recent observations suggest that commensal bacteria can also enhance anti-tumor T cell responses following chemotherapy.…”
Section: Discussionmentioning
confidence: 89%
“…We did not perform monocolonization experiments in our system, and thus it is entirely possible that SFB acts here indirectly, as observed in models of colitis 13 or type 1 diabetes. 37 The most interesting result from this study, however, is the unique regulation of a T-cell intrinsic tolerance mechanism achieved by SFB-derived inflammatory signals. Recent observations suggest that commensal bacteria can also enhance anti-tumor T cell responses following chemotherapy.…”
Section: Discussionmentioning
confidence: 89%
“…In NOD mice, gluten free diet changes microbial communities in the gut and lowers the incidence of diabetes [117]. NOD mice that receive acidified rather than neutral drinking water show an altered compostion of gut microbiota that is associated with more suceptiblity to the development of insulitis and hyperglycemia [118]. Diet in the long run has an influence on the balance of major bacterial phyla by changing the ratio of Bacteroides to Firmicutes in the gut [108].…”
Section: Nutrition and Obesitymentioning
confidence: 99%
“…Fecal microbiota transplantation has shown to be promising in the treatment of Clostridium difficile infections [127]. Fecal transfer from SFB positive donors suppresses type 1 diabetes in recipient NOD mice [118].…”
Section: Therapeutic Interventions Probiotics and Microbiomementioning
confidence: 99%
“…We recently described that drinking water pH influences the composition of gut microbiota and type 1 diabetes (T1D) incidence in nonobese diabetic (NOD) mice (1,2). In a study conducted at the specific pathogen-free (SPF) facilities of University of Illinois at Chicago (UIC) and Medical University of South Carolina (MUSC), Sofi et al (1) reported an association between consumption of acidic drinking water (AW) and high diabetes incidence in NOD mice obtained from The Jackson Laboratory (JAX) and mice from the breeding colonies of UIC and MUSC.…”
mentioning
confidence: 99%